Between politics and poetics: Topics of the Crimea in contemporary Russian-speaking naïve poems - R. Leibov; B. V. Orekhov (Шаги)
Naïve poetry, that is, poetry that has not passed through editorial filters, published by the authors on the Internet (on the website stihi.ru), provides unique material for the study of natural interpretations of important political events. The article analyzes poems in which the word “Crimea” is mentioned, from the website stihi.ru, for the period 2000–2019. These poems are processed using the technology of topic modeling. The essence of this technology is that in a large collection there are co-occurring words, usually semantically close within a certain unified context. A series of such words serve as representations of “topics”, that is what characterizes the text from a semantic point of view. The sample was divided into several stages and a model of 5 themes was built for each. For the Crimea, one of the main topics is that of paradise on earth. It is the topic that unites most of the poems written before the events of 2014. After 2014, in works by amateur authors we observe the invasion of current topics into the established world of the resort; the latter does not disappear, but gives way to politics. Five years later, political topics remain, but landscape and love lyrics return as well. On the topical level, we do not trace a clear influence of “high” poetry on the authors of stihi.ru. Traditional in form (verse division, rhythm, rhyme), the response of naïve poets breaks sharply with the literary tradition of substantive embodiment of such a response. Topic modeling allows us to evaluate the transformation of the Crimean plot in that segment of public consciousness which is reflected in the production of naïve poets.